The Effectiveness of Restitution Fulfillment for Children as Sexual Crime Victims: A Study in the North Maluku High Prosecutor’s Office - Malik, Faissal; Hanafi, Muhammad Amin; Papuluwa, Nurlaila Kadarwati; Budiono, Arief (JURNAL USM LAW REVIEW, 2024)
This paper aims to analyze the implementation of restitution right fulfillment for children as sexual crime victims in the legal area of the North Maluku High Prosecutor’s Office, Indonesia and the challenges in fulfilling these rights. Restitution is compensation given to the victim by the perpetrator of the crime or a third party and is an effort to guarantee the rights of victims. There was an issue where restitution rights were seldom strived for by law enforcers. Another problem is that society lacks knowledge of the existence of restitution rights. This paper is urgent because it may provide information on why these issues exist and how to resolve them in order to give victims their rights. This was empirical research which employed the statute approach and the case approach. In this paper, the live case study was applied. Results showed that the restitution fulfillment of children as sexual crime victims in the North Maluku High Prosecutor’s Office was still suboptimum as there was only one case in 2022 where the general prosecutor strived to demand restitution. The restitution is regulated in Governmental Regulation No. 43 of 2017 and Guidelines Supreme Court No. 1 of 2021. Law enforcing apparatuses and social institutions need to organize an education program for society on restitution rights for children as sexual crime victims in the North Maluku Province to increase their awareness. The application for restitution should be strived for by law enforcers starting from the investigation stage as more time is available.